2020
DOI: 10.1088/1757-899x/808/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Malachite Green Dye by Plant-mediated Biosynthesized Zinc Oxide Nanoparticles

Abstract: Photocatalytic activity of ZnO-NPs was tested by degradation of Malachite Green dye under UV light irradiation. The ZnO-NPs were biosynthesized using Punica granatum (pomegranate) fruit peels extract as the stabilizing agent. Simple sol-gel method and calcination in different temperatures (400, 500, 600 and 700°C) were carried out to obtain pure ZnO-NPs with high photocatalytic properties. In the degradation studies, 20 mg ZnO-NPs were used to degrade Malachite Green dye of 10 ppm initial concentration for a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In vivo evaluation in mice skin confirmed that the CS/PVA/ZnO dressings appeared faster wound healing, and more complete when compared with that of pure chitosan, and CS/PVA. In addition, the influences of ZnO-NPs on fibroblast cell growth (NIH3T3) as a wound healing activity was conducted [54]. The results proved that the growth of fibroblast cell is higher with ZnO nanoparticles of larger particle size.…”
Section: Wound Healingmentioning
confidence: 94%
“…In vivo evaluation in mice skin confirmed that the CS/PVA/ZnO dressings appeared faster wound healing, and more complete when compared with that of pure chitosan, and CS/PVA. In addition, the influences of ZnO-NPs on fibroblast cell growth (NIH3T3) as a wound healing activity was conducted [54]. The results proved that the growth of fibroblast cell is higher with ZnO nanoparticles of larger particle size.…”
Section: Wound Healingmentioning
confidence: 94%
“…Calcination temperature is another synthesis parameter that has an effect on the morphology, size, and properties of ZnO NPs. Sukri and associates [52] studied the influence of calcination temperature on the morphology and size of ZnO NPs synthesised using Punica granatum fruit peel. The synthesised ZnO NPs were calcined from 400 to 700 • C, and the authors reported that increasing calcination temperature produced irregularly shaped NPs and an increase in the size of NPs, whereas spherical NPs were observed at lower temperatures using TEM.…”
Section: Factors Affecting Synthesis Of Plant-mediated Zno Npsmentioning
confidence: 99%
“…The photocatalytic assessment was studied by considering the achieved results with low dye concentration of MG as given in Table 3 [55][56][57][58][59][60][61][62][63][64][65][66][67][68]. And the obtained results are equal or superior to the reported works in terms of performance, low-cost fabrication, simple and green nature of material synthesis approach.…”
Section: Effect Of Initial Dye Concentrationmentioning
confidence: 99%